Does it pay to be one of the oldest in class? Relative age effects on academic self-concept, peer relations, and teacher judgments in German primary schools. (August 2021) - Kretschmann, Julia; Westphal, Andrea; Vock, Miriam
Abstract: Several studies have revealed that older students in a year group reach higher achievement scores than younger students in that group. But less is known about how students' relative age in class relates to their self-perception of academic achievement, their social acceptance in class and to how teachers judge their abilities. Therefore, we examined relative age effects within class on students' academic self-concept, peer relations, grades, and teachers' secondary school recommendation. Analyses were based on a sample of N  = 18, 956 German fourth graders, who had never been retained or accelerated. We applied multilevel regression to control for covariates at the individual and classroom level. There were no substantial relative age effects within class across any of the outcomes, except for a small advantage for the youngest in their reading self-concept. Our findings therefore contradict the common assumption that younger students in class are disadvantaged compared to their older classmates. Highlights: We examined peer relations, academic self-concept, grades, and track recommendations. We found no considerable relative age effects favoring older students in class. The youngest in class had higher reading self-concepts than the oldest in class. Controlling for covariates (e.g., achievement) made no difference in the results.